Menelisik Legalitas Perkawinan Beda Agama di Indonesia: Analisis Yuridis dan Implikasinya dalam Hukum Perkawinan - Muzakkir, Muzakkir; Muzakir, Kahar; Muhazir, Muhazir (Jurnal El-Thawalib, 2025)
The legality of interfaith marriage in Indonesia remains a controversial issue, reflecting the legal uncertainty faced by couples of different religious backgrounds. Regulatory ambiguity has led to an increase in applications for marriage validation in court, indicating the need to re-evaluate the principle of legality within the national legal system. This study aims to offer a new perspective that distinguishes it from previous research by analyzing and highlighting the regulatory ambiguity surrounding interfaith marriage in Indonesia. This is a normative legal study employing a juridical-normative approach. Primary data is derived from Law No. 1 of 1974 on Marriage and Law No. 23 of 2006 on Population Administration; secondary data includes legal literature, journals, and empirical research directly related to the topic. Data is collected through literature review and analyzed using a descriptive-analytical method. The findings indicate a legal vacuum and normative inconsistencies that complicate the registration and legal recognition of interfaith marriages. From the perspective of Islamic law, the majority of scholars declare such marriages invalid, particularly when the woman is a Muslim, based on Qur'anic verse Al-Baqarah 2:221. In judicial practice, jurisprudence such as Supreme Court Decision No. 1400 K/Pdt/1986 affirms that the validity of marriage must be based on the provisions of each party’s religion. Meanwhile, actual cases show that some couples marry abroad and subsequently register the marriage in Indonesia as a shortcut to bypass domestic legal barriers. This study recommends harmonizing regulations between the Marriage Law and the Population Administration Law, formulating specific norms on interfaith marriage, and strengthening the role of religious and judicial institutions in providing legal clarity, certainty, and inclusive justice.